Quasigroup string processing: Part 4 - Markovski, Smile; Bakeva, Verica (My University, 2017)
Given a finite alphabet A and a quasigroup operation ∗ on the set A, in earlier paper of ours we have defined the quasigroup transformation E : A + → A +, where A + is the set of all finite strings with letters from A. Here we present several generalizations of the transformation E and we consider the conditions under which the transformed strings have uniform distributions of n-tuples of letters of A. The obtained results can be applied in cryptography, coding theory, defining and improving pseudo random generators, and so on.
Keywords: quasigroup, quasigroup string processing, uniform distribution